Gambaran Variasi Menu Dan Tingkat Kepuasan Konsumen Di Taman Sari Sakato Katering Kota Pekanbaru - Fitriani Fitriani; Shisi Tridestia; Esthy Rahman Asih; Aslis Wirda Hayati (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2021)
Background : Complete menu ranging from taste, type of food and drink, and product availability at any time, it will be able to attract the attention of consumers to make a purchase and make it easier for consumers to choose various kinds of menus to their liking. The Purpose : This study aims to determine how the description of menu variations and the level of consumer satisfaction in Taman Sari Sakato Catering Pekanbaru City. Methods : This type of research is a descriptive study with a cross sectional survey research design. The study was conducted in January to April at Taman Sari Sakato Catering Pekanbaru City with a total sample of 60 by accidental sampling. Results : The results of the study using a Likert scale calculation obtained a percentage score of 75.6% (good) on the menu variations and 75.16% (satisfied) to the level of consumer satisfaction in Caterer Taman Sari Sakato, Pekanbaru City. Conclusion : The description of menu variations in Taman Sari Sakato Catering Catering is in good criteria while the description of the level of consumer satisfaction in Taman Sari Sakato Catering is in the satisfaction criteria. Suggestions : It is recommended that further research need to add education and employment criteria to the characteristics of respondents in the questionnaire. It is also necessary to make open-ended questions on the questionnaire in order to find out the reasons for the negative answers given by respondents.